2022
DOI: 10.3390/toxins14090646
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of Chitinases from Xenorhabdus nematophila HB310 and Its Relationship with the Toxin Complex

Abstract: Xenorhabdus nematophila HB310 secreted the insecticidal protein toxin complex (Tc). The chi60 and chi70 chitinase genes are located on the gene cluster encoding Tc toxins. To clarify the insecticidal activity of chitinases and their relationship with Tc toxins, the insecticidal activity of the chitinases was assessed on Helicoverpa armigera. Then, the chi60 and chi70 genes of X. nematophila HB310 were knocked out by the pJQ200SK suicide plasmid knockout system. The insecticidal activity of Tc toxin from the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In particular, XnChi is relatively close to the X. nematophila ATCC19061 chitinase (Genbank accession number: WP 010846090.1), which shows 99.69% homology to Chi70 (Genbank accession number: GK44779.1) of X. nematophila . Chi70 was reported to have insecticidal and antifungal activities against certain pests and fungi, and to improve insecticidal activity of BtCryAc and Tc toxins [ 23 , 31 , 32 ]. Thus, symbiotic bacterial chitinases of EPNs could be promising control agents of insect pests and plant pathogenic fungi by playing an important role in pesticidal activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, XnChi is relatively close to the X. nematophila ATCC19061 chitinase (Genbank accession number: WP 010846090.1), which shows 99.69% homology to Chi70 (Genbank accession number: GK44779.1) of X. nematophila . Chi70 was reported to have insecticidal and antifungal activities against certain pests and fungi, and to improve insecticidal activity of BtCryAc and Tc toxins [ 23 , 31 , 32 ]. Thus, symbiotic bacterial chitinases of EPNs could be promising control agents of insect pests and plant pathogenic fungi by playing an important role in pesticidal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, chitinase’s key enzyme has received increasing attention as biopesticide for the control of insect pests and fungal diseases because chitin synthesis is performed using a range of organisms, including fungi and insects, and key enzyme in biosynthesis [ 21 , 22 ]. Chitinase is a Glycoside hydrolase (GH) that acts to degrade chitin using hydrolyzing glycosidic bonds [ 23 ], and it is classified into two main groups, chitinase (EC3.2.1.14) and β-acetylhexosaminidase (EC 3.2.1.52), officially called endochitinase and exochitinase, respectively, depending on the products produced during the hydrolysis process [ 24 , 25 ]. Endochitinase cleaves into the chitin chain at an internal site.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the aforementioned studies indicated that secondary metabolites of different Xenorhabdus and Photohabdus species were able to penetrate through the cuticle and cause remarkable mortalities against tested insects with a varying degree of pathogenicity [44,75,76,83]. Chitinase protein secreted by Xenorhabdus and Photorhabdus bacteria plays a key role in the virulence of symbiotic bacteria by both degrading the cuticles of insects and accelerating the binding process of toxins to target sites [84,85]. The results suggest that toxic metabolites including chitinase protein are present in the cell-free supernatant of symbiotic bacteria and are responsible for mortality.…”
Section: Discussionmentioning
confidence: 99%